Mapas conceituais e aprendizagem de conteúdo escolar no ensino fundamental I - Falcão, Rejane Maria de Araújo Lira (2012)
This research is the result of an experiment accomplished with Elementary students from the fifth year, of a Municipal Public School from João Pessoa PB. It aimed at developing teaching methodologies based on David Ausubel´s Meaningful Verbal Learning Theory (MVLT) to make viable learning of school contents in a meaningful way, adopting, as tool for this learning, the construction of conceptual maps. Experimentation occurred by means of Natural Sciences curricular component, in which Human Reproduction was explored as content. The used methodology refers to the basic, experimental research approach, with experimental guideline, and field strategies concerning information source and data collection of longitudinal temporality as well as quantitative and qualitative nature. For data collection a pre and a post test, in questionnaire form, were carried out. The first one intended to select students´ previous knowledge; and the second one to measure fulfilled changes. Semistructured interviews with the experimental group aiming at analyzing the built learning, from the students´ conception, were also fulfilled. By perceiving the specificity of the object of this study, it also prompts dialogue with those who took part in the process. Results pointed out, with no doubt, that the conceptual maps influenced meaningfully learning of the explored school content and they suggest that the mentioned experience is a strategy that offers perspectives of improvement of educational practices and serves as instrument for the advancement of investigations about teaching-learning processes.